2012
DOI: 10.1111/j.1755-3768.2012.t017.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visual impairment among the elderly: can it be corrected?

Abstract: Purpose To determine the prevalence of visual impairment,low vision and blindness among the elderly of Sari in north of Iran. Methods Through cluster random sampling, 60 clusters were selected, out of which 20 people were systematically selected for this study. Participants received eye examinations including vision, actual visual acuity (AVA), optimal visual acuity (OVA) and refraction. Non‐cycloplegic refraction was performed with an auto refractometer and the results were checked with retinoscopy and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…According to Table 4, which presents the prevalence of VI in similar studies, the prevalence of VI in our study was higher than some (de Winter et al, 2004; Friedman et al, 2004; Horowitz, 1994; Mitchell et al, 1997; Owsley et al, 2007a; Tielsch et al, 1995; West et al, 2003; Whitmore, 1989) and lower than some other studies (VanNewkirk et al, 2000; Waked, Saad, Mehanna, Sleilaty, & Kortbaoui, 2007), which could be due to differences in the definition or ethnicity and race of the participants. On the other hand, the prevalence of VI in our participants was 4–20 times higher when compared to its prevalence in similar age groups of community-dwelling people, as domestic studies have reported a prevalence of 2–11% (Hashemi, Khabazkhoob, Emamian et al, 2012; Hashemi, Khabazkhoob, Saatchi, Ostadimoghaddam, Yekta, 2017; Hashemi, Yekta, et al, 2017; Yekta et al, 2011; Yekta, Hashemi, Ostadimoghaddam, Shafaee, Norouzirad, Radaye-moghaddam, et al, 2013), which is far lower than our results. In line with our study, some other studies have also reported a higher prevalence of VI in NHRs as compared to community-dwelling older persons (de Winter et al, 2004; Horowitz, 1994; Klein et al, 1991; Mitchell et al, 1997; Owsley et al, 2007a; Taiel-Sartral et al, 1999; Tielsch et al, 1995; Van der Pols et al, 2000; VanNewkirk et al, 2000; West et al, 2003; Whitmore, 1989).…”
Section: Discussioncontrasting
confidence: 90%
“…According to Table 4, which presents the prevalence of VI in similar studies, the prevalence of VI in our study was higher than some (de Winter et al, 2004; Friedman et al, 2004; Horowitz, 1994; Mitchell et al, 1997; Owsley et al, 2007a; Tielsch et al, 1995; West et al, 2003; Whitmore, 1989) and lower than some other studies (VanNewkirk et al, 2000; Waked, Saad, Mehanna, Sleilaty, & Kortbaoui, 2007), which could be due to differences in the definition or ethnicity and race of the participants. On the other hand, the prevalence of VI in our participants was 4–20 times higher when compared to its prevalence in similar age groups of community-dwelling people, as domestic studies have reported a prevalence of 2–11% (Hashemi, Khabazkhoob, Emamian et al, 2012; Hashemi, Khabazkhoob, Saatchi, Ostadimoghaddam, Yekta, 2017; Hashemi, Yekta, et al, 2017; Yekta et al, 2011; Yekta, Hashemi, Ostadimoghaddam, Shafaee, Norouzirad, Radaye-moghaddam, et al, 2013), which is far lower than our results. In line with our study, some other studies have also reported a higher prevalence of VI in NHRs as compared to community-dwelling older persons (de Winter et al, 2004; Horowitz, 1994; Klein et al, 1991; Mitchell et al, 1997; Owsley et al, 2007a; Taiel-Sartral et al, 1999; Tielsch et al, 1995; Van der Pols et al, 2000; VanNewkirk et al, 2000; West et al, 2003; Whitmore, 1989).…”
Section: Discussioncontrasting
confidence: 90%
“…This is while according to Bastawrous et al, population-based studies in 15 African countries have found cataracts to be the leading cause of uncorrected visual impairment in the over 50 population, and Ghana has the highest prevalence (more than 80%) of cataract-related vision impairment. 23 In Shahroud, Sari, and Khaf studies, the prevalence of cataracts based on presenting vision was respectively 20.2%, 13 16.7%, 24 and 27.6%, 12 which points to a lower prevalence of cataracts in Mashhad compared to rural regions. Although the prevalence of cataracts in the present study is higher than in Sari and Shahroud studies, it should be noted that only the over 50 population was included in Sari, and the age distribution of the sample in Shahroud was 40–64 years.…”
Section: Discussionmentioning
confidence: 91%
“…Among the few population-based studies conducted in urban areas of the country, the studies in Shahroud (40–64 year old age group) and Sari have reported the main causes of visual impairment based on uncorrected visual acuity, and in agreement with our study, they have stated it to be uncorrected refractive errors. 13 , 24 Also, in a study by Hashemi et al 12 in rural areas of Khaf in the northeast of Iran, refractive errors were the leading cause with a prevalence of 57%. As shown in Table 5 , various studies indicate that uncorrected refractive errors are the major cause of visual impairment based on presenting vision in the six WHO regions including developing and developed member states.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence showed that difficulties in seeing increased significantly in the individual aged 50 and above compared to younger age groups [10]. It was noted that lack of access to ophthalmologic facilities and services among older group was a major reason for almost finding, considering the fact that most diseases occur in the fifth decade of life [14]. Study done in Poland, also stated that visual impairment was found in 27.5% subjects in the worse-seeing eye and showed the increasing age and female gender were independent risk factors [15].…”
Section: Discussionmentioning
confidence: 99%